2022
DOI: 10.21037/cdt-21-590
|View full text |Cite
|
Sign up to set email alerts
|

Early surgery determines prognosis in patients with infective endocarditis: outcome in patients managed by an Endocarditis Team—a prospective cohort study

Abstract: Background: Infective endocarditis (IE) in South Africa is associated with significant morbidity and mortality, despite occurring in younger patients with fewer co-morbidities. Possible contributors include the high rates of blood culture negative endocarditis, high rates of mechanical valve replacement and the lack of inter-disciplinary coordination during management. Methods:The Tygerberg Endocarditis Cohort (TEC) study prospectively enrolled patients with IE between November 2019 and April 2021. All patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 39 publications
0
4
1
Order By: Relevance
“…This cluster of cases was notable for the aggressive nature of the infection and high mortality. A recent prospective cohort of 72 IE cases in the Western Cape described an in-hospital mortality rate of 18% 22 in contrast to the 80% mortality rate observed in our cohort. Only one individual survived, likely because of early identification and prompt surgical intervention (within 24 h of diagnosis).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…This cluster of cases was notable for the aggressive nature of the infection and high mortality. A recent prospective cohort of 72 IE cases in the Western Cape described an in-hospital mortality rate of 18% 22 in contrast to the 80% mortality rate observed in our cohort. Only one individual survived, likely because of early identification and prompt surgical intervention (within 24 h of diagnosis).…”
Section: Discussioncontrasting
confidence: 99%
“…The high rate of complications and relentless progression of disease despite appropriate, directed antibiotic therapy highlights the importance of surgical management of IE. 22 Although the pathogenesis of non-toxigenic C. diphtheriae infection remains obscure, it seems likely that other virulence factors replace toxin production in these strains. Differences in protein secretion related to synthesis of pili and cellular adherence and invasion may contribute to virulence in some strains.…”
Section: Discussionmentioning
confidence: 99%
“…Surgical management of endocarditis remains to be challenging and is related with significant morbidity and mortality. [ 11 , 12 ] Univariable and multivariable analyses also showed that prolonged ICU stay is statistically significantly related to acute renal injury, prolonged intubation time, in-hospital mortality, and 1-year mortality (Table 6 ). Determining the risk factors of prolonged ICU stay has clinical significance for the management of IE.…”
Section: Discussionmentioning
confidence: 97%
“…During fluid administration, cardiac function needs to be closely monitored either with cardiac output monitoring or echocardiography. [ 11 , 14 ]…”
Section: Discussionmentioning
confidence: 99%
“…The ideal timing for surgery in patients with IE is still uncertain. Nevertheless, early surgical intervention has been linked to a lower risk of mortality ( 6 , 7 ). In patients with IE, prompt surgical treatment can decrease the risk of bacterial emboli and thromboembolic events, as well as related complications ( 6 ).…”
Section: Introductionmentioning
confidence: 99%